Mineralocorticoid Receptor Antagonist (Potassium Canrenoate) Does Not Influence Outcome in the Treatment of COVID-19-Associated Pneumonia and Fibrosis-A Randomized Placebo Controlled Clinical Trial - Katarzyna Kotfis; Igor Karolak; Kacper Lechowicz; Małgorzata Zegan-Barańska; Agnieszka Pikulska; Paulina Niedźwiedzka-Rystwej; Miłosz Kawa; Jerzy Sieńko; Aleksandra Szylińska; Magda Wiśniewska (MDPI AG, 2022)
In December 2019 the SARS-CoV-2 virus appeared in the world, mainly presenting as an acute infection of the lower respiratory tract, namely pneumonia. Nearly 10% of all patients show significant pulmonary fibrotic changes after the infection. The aim of this study was to evaluate the effectiveness and safety of potassium canrenoate in the treatment of COVID-19-associated pneumonia and pulmonary fibrosis. We performed a randomized clinical trial (RCT) of potassium canrenoate vs placebo. A total of 55 patients were randomized and 49 were included in the final analysis (24 allocated to the intervention group and 25 allocated to the control group). Patients were assessed by physical examination, lung ultrasound, CT imaging and blood samples that underwent biochemical analysis. This RCT has shown that the administration of potassium canrenoate to patients with COVID-19 induced pneumonia was not associated with shorter mechanical ventilation time, shorter passive oxygenation, shorter length of hospitalization or less fibrotic changes on CT imaging. The overall mortality rate was not significantly different between the two groups. Adverse events recorded in this study were not significantly increased by the administration of potassium canrenoate. The negative outcome of the study may be associated with the relatively small number of patients included. Any possible benefits from the use of potassium canrenoate as an antifibrotic drug in COVID-19 patients require further investigation.